Health Care Behaviors of the Elderly in the Community Receiving Health Care by a Multidisciplinary Team - Sadubpod, Kamala; Kochsiripong, Patchaya (Journal of Health Science of Thailand, 2019)
The aim of this study was to assess the health care behaviors, food consumption and medical treatment of the elderly in a community receiving health care by multidisciplinary team at Sinsamut community, Pathumthani province. The research methodology was cross-sectional descriptive research. Data were collected from the elderly lived in Sinsamut community between August to December 2017 using a questionnaire. This community model had established an elderly club, sport competition including home visit from a multidisciplinary team. The results showed that there were 60 elderly subjects. Most of them were female and had the good health care behaviors, especially the food consumption, daily bodily movement, non-smokng or drinking alcohol, dislike drinking sweet drinks or soft drinks, and visiting the doctor when having illness. Nevertheless, routine exercise and weight control was performed in only 53.30% and 28.30% of them, respectively. In addition, blood pressure control in hypertension patients with diabetes or chronic kidney disease still was not in line with the standard criteria. Furthermore, the study showed that the age was significantly correlated with body mass index (p<0.05). Elderly with body mass index 25 kg/m2 and above were aged 60-69 years. The factors associated with chronic non-communicable disease were the largest meal (p<0.01), source of the diets (p<0.05), consumption of caffeinated beverages (p<0.05), and visiting the doctor only when having illness (p<0.01). It could be concluded that Sinsamut community, Pathumthani province, had developed a community health care model that enabled the elderly to control their consumption proporly and to visit doctor regularly. This elderly health care model should be widely implemented in other communities.